2017
DOI: 10.1038/s41598-017-13678-5
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Associated Immunoglobulin-like Receptor-1 is regulated in human myocardial infarction but its absence does not affect infarct size in mice

Abstract: Heart failure after myocardial infarction (MI) depends on infarct size and adverse left ventricular (LV) remodelling, both influenced by the inflammatory response. Leukocyte-associated immunoglobulin-like receptor 1 (LAIR-1) is an inhibitory receptor of ITAM-dependent cell activation, present on almost all immune cells. We investigated regulation of LAIR-1 leukocyte expression after MI in patients and hypothesized that its absence in a mouse model of MI would increase infarct size and adverse remodelling. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Since an exacerbated inflammatory response might be potentially harmful, the control of the pro-inflammatory mechanisms by an anti-inflammatory counterbalance is an important protective process against further enhancement of inflammation (50,51). Our different in vitro and in vivo models indicate that inflammation leads to an upregulation of LAIR-1, as observed here in monocytes from sepsis patients, but also on circulating monocytes in acute myocardial infarction, rheumatoid arthritis and liver cirrhosis (52)(53)(54). The upregulation of LAIR-1 during inflammation, for instance mediated by TLR or IFN signals, will facilitate its inhibitory signals.…”
Section: Discussionmentioning
confidence: 53%
“…Since an exacerbated inflammatory response might be potentially harmful, the control of the pro-inflammatory mechanisms by an anti-inflammatory counterbalance is an important protective process against further enhancement of inflammation (50,51). Our different in vitro and in vivo models indicate that inflammation leads to an upregulation of LAIR-1, as observed here in monocytes from sepsis patients, but also on circulating monocytes in acute myocardial infarction, rheumatoid arthritis and liver cirrhosis (52)(53)(54). The upregulation of LAIR-1 during inflammation, for instance mediated by TLR or IFN signals, will facilitate its inhibitory signals.…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have demonstrated that the expression of TNFSF14, 54 ITGAL (integrin subunit alpha L), 55 PLAC8, 56 ADRA2A, 57 CCL21, 58 ALOX5, 59 CNR2, 60 COL1A1, 61 WNT7A, 62 SLAMF1, 63 CD3D, 64 lactotransferrin (LTF), 65 MIR27B, 66 PDK4, 67 UCN3, 68 PCK1, 69 carboxyl ester lipase (CEL), 70 TRPM6, 71 microsomal triglyceride transfer protein (MTTP), 72 CYP2 C8, 73 and CYP3A4 74 is associated with progression of type 2 diabetes mellitus. Recent studies have proposed that the altered expression of MZB1, 75 LAIR1, 76 MIR142, 77 and fibroblast activation protein alpha (FAP) 78 has been shown to be a meaningful advance factor for myocardial infarction. IRF4 plays a key role in obesity-induced insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…TNFSF14 [47], ITGAL (integrin subunit alpha L) [48], PLAC8 [49], ADRA2A [50], CCL21 [51], ALOX5 [52], CNR2 [53], COL1A1 [54], WNT7A [55], SLAMF1 [56], CD3D [57], LTF (lactotransferrin) [58], MIR27B [59], PDK4 [60], UCN3 [61], PCK1 [62], CEL (carboxyl ester lipase) [63], TRPM6 [64], MTTP (microsomal triglyceride transfer protein) [65], CYP2C8 [66] and CYP3A4 [67] have important role in the progression of type 2 diabetes via in ammation , but these genes might be crucial role in DN progression. Zhang et al [68], Ellenbroek et al [69], Guo et al [70] and Tillmanns et al [71] have shown that MZB1, LAIR1, MIR142 and FAP ( broblast activation protein alpha) modulating mitochondrial function and alleviating in ammation in myocardial infarction, but these genes might be involved in progression of DN. IRF4 plays a key role in the obesity-induced insulin resistance [72], but this gene might be responsible for development of DN.…”
Section: Discussionmentioning
confidence: 99%